Evaluation of virtual instructional designs for mathematics didactic units - Zambrano-Leal, Newman (2023)
The objective of the research was to develop an instrument for assessing the instructional design quality of virtual classrooms created by undergraduate students majoring in Mathematics Education for Secondary Education, with the aim of enhancing mathematics education at that level. The instrument was validated using a quantitative methodology, which included expert evaluations and internal consistency based on 237 assessments of 21 virtual classrooms. The instrument is based on criteria improvements from Spain's INTEF, evaluating didactic description, content quality, adaptability, interactivity, motivation, format and design, navigation, and accessibility of audiovisual content, with adaptations made for improvement. High validity and reliability were achieved. The instrument allows for the evaluation of didactic units in the Dominican mathematics curriculum at the secondary level. This research promotes effective instructional design in virtual classrooms, thereby preventing confusion and frustration among students in poorly designed online courses.